2008
DOI: 10.1007/s10531-008-9516-z
|View full text |Cite
|
Sign up to set email alerts
|

Managing genetic variation in tropical trees: linking knowledge with action in agroforestry ecosystems for improved conservation and enhanced livelihoods

Abstract: Tree species in agroforestry ecosystems contribute to the livelihoods of rural communities and play an important role in the conservation of biodiversity. Unless agroforestry landscapes are productive, however, farmers will not maintain or enhance the range and quality of tree species in them, and both income opportunities and biodiversity will be lost. Productivity depends on both tree species diversity and genetic (intra-speciWc) variation, but research on the latter has until recently not received the recog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
58
0
6

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(64 citation statements)
references
References 73 publications
0
58
0
6
Order By: Relevance
“…Support from NGOs should therefore come through greater focus on the establishment of good quality (rather than unknown quality) seed sources. It should extend to providing business training to entrepreneurial seed dealers and tree nurseries, and should support networks of producers and distributors of seed and seedlings (Dawson et al 2009;Kindt et al 2006). The role of NGOs is also to support the development of smallholder product value chains through better linkages with markets; this in turn will drive better input supply chains.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Support from NGOs should therefore come through greater focus on the establishment of good quality (rather than unknown quality) seed sources. It should extend to providing business training to entrepreneurial seed dealers and tree nurseries, and should support networks of producers and distributors of seed and seedlings (Dawson et al 2009;Kindt et al 2006). The role of NGOs is also to support the development of smallholder product value chains through better linkages with markets; this in turn will drive better input supply chains.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, for the majority of potential tree crops, equivalent farmer-to-farmer production and distribution of seed is a less feasible configuration than for annuals. Furthermore, this approach carries particular risks for outbreeding tree species that are potentially subject to inbreeding depression in farmland, if genetic bottlenecks arise through narrow a As several species occur in more than one type of source, numbers for individual categories are different from the overall totals diffusion (Dawson et al 2009;Dhakal et al 2005). A commercial 'Decentralised Model' introducing new species and varieties therefore requires special attention to how tree seed sources are utilised as breeding, foundation, and commercial seed in the input supply chains.…”
Section: Agroforestry Seed-sources and Definitionsmentioning
confidence: 99%
“…In addition, different anthropogenic factors and natural phenomenon such as death due to drought, fungal diseases and destruction by elephants have shaped genetic diversity within the populations (Guy (1971;Wilson 1988;Edkins et al 2007). Furthermore, differences in time of tree flowering within and between populations happening in Malawi may reduce the effective number of trees in baobab populations differently; setting in varying degrees of random drift impacting on genetic diversity (Dawson et al 2009). Mwase et al (2006) indicated that distribution range and population size have strong relationship within population genetic variation in tropical tree species with restricted populations displaying significantly less variation than those with wide distribution.…”
Section: Allelic Diversitymentioning
confidence: 99%
“…Wild trees are genetically structured through natural processes such as mutation, genetic drift, selection, reproductive isolation, and migration (Buiteveld et al 2007). Plant molecular studies have shown that fragmentation of habitats and small population sizes negatively affect population genetic diversity (Dawson et al 2009). For instance, the genetically less diverse populations have reduced chance to buffer the effects of poor environmental conditions or competitions (Pluess and Stöcklin 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Assessment of vegetation level vulnerability, climate change resilience and human adaptation options requires understanding of the diversity, among tree species in the current vegetation, of genetic and phenotypic growth strategies and response to fluctuating water availability (Dawson et al 2009). Human livelihoods in many parts of Africa depend on the use and management of trees in forms of dryland agroforestry (Poschen 1986).…”
Section: Introductionmentioning
confidence: 99%